P.A.R.A.S.I.T.E. Museum : Gyüjteménye. - Mücsarnok, Budapest; Museum Bochum; The Central House of Artists, Moscow (Ljubljana : Moderna galerija Lubljana, 1995)
Barsi, Joze ; Bratusa, Mirko ; Irwin ; Kirbis, Dusan ; Kovacic, Marko ; Pogacar, Tadej ; Potrc, Marjetica ; Simoncic, Petra Varl ; V.S.S.D.
P.A.R.A.S.I.T.E. Museum : Gyüjteménye / Sammlung / Collection, Mücsarnok, Budapest, oktober 19 - november 19, 1995 / Museum Bochum, 13. Januar - 3. März 1996 / The Central House of Artists, Moscow, 15 May - 5 June 1995
boek